Chronobiological Hypothesis about the Association Between Height Growth Seasonality and Geographical Differences in Body Height According to Effective Day Length. (11th November 2016) - Yokoya, Masana; Higuchi, Yukito
Studies on growth hormone therapy in children have shown that height velocity is greater in summer than in winter and that this difference increases with latitude. It is hypothesized that summer daylight is a causative factor and that geographical distribution of body height will approximate the distribution of summer day length over time. This is an ecological analysis of prefecture-level data on the height of Japanese youth. Mesh climatic data of effective day length were collated. While height velocity was greatest during the summer, the height of Japanese youth was strongly and negatively correlated with the distribution of winter effective day length. Therefore, it is anticipated that summer height velocity is greater according to winter day length (dark period). This may be due to epigenetic modifications, involving reversible DNA methylation and thyroid hormone regulation found in the reproductive system of seasonal breeding vertebrates. If the function is applicable to humans, summer height growth may quantitatively increase with winter day length, and height growth seasonality can be explained by thyroid hormone activities that-induced by DNA methylation-change depending on the seasonal difference in day length. Moreover, geographical differences in body height may be caused by geographical differences in effective day length, which could influence melatonin secretion among subjects who spend a significant time indoors.